Polymer coupling via hetero-disulfide exchange and its applications to rewritable polymer brushes - Sim, Xuan Ming (2021)
An iodide-terminated polymer (Polymer-I) is converted to a thiol-terminated polymer (Polymer-SH) using HSCH2CH2SH in a remarkably short time (10 min). Polymer-SH is further converted to a pyridyl disulfide-terminated polymer (Polymer-SS-Py). The hetero-coupling of Polymer-SH and Polymer-SS-Py is successfully achieved to quantitatively generate a polymer disulfide (Polymer-SS-Polymer). Exploiting this efficient hetero-coupling technique, Polymer-SH is attached (grafted) on a Py-SS-immobilized surface to generate a polymer brush via a disulfide (-SS-) linkage (writing process). The -SS- linkage is cleaved by the treatment with dithiothreitol (DTT) to detach the polymer from the surface (erasing process). Subsequently, another Polymer-SH is attached on the surface to generate another polymer brush (rewriting process). Thus, a writable, erasable, and rewritable polymer brush surface is achieved. Hydrophilic, hydrophobic, and super-hydrophobic polymers (Polymer-SH) are attached on the surface, tailoring the surface wettability in the writing-erasing-rewriting cycles. Polymer-SH is also attached on a chain-end Py-SS-functionalized polymer brush surface, generating a rewritable block copolymer brush surface. A patterned block copolymer brush surface is also obtained using photo-irradiation and a photo-mask in the erasing process. The metal-free synthetic procedure, accessibility to patterned brushes, and switchable surface properties via the writing-erasing-rewriting process are attractive features of the present approach.